Proteins of the cerebrospinal fluid : analysis and interpretation in the diagnosis and treatment of neurological disease - Thompson, E. J., 1940-; Thompson, E. J.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier Academic Press, 2005)
The analysis of the protein content of the Cerebrospinal Fluid (CSF) is a central tool in the diagnosis of a number of diseases, including Multiple Sclerosis and Encephalitis. This book is a complete revision of the first edition published 16 years ago and reflects the advances in the field in that period. Containing the most comprehensive reference list available today with over 1300 references cross-indexed according to topics, it also includes many classical works that cannot be easily found through the public literature database (like PubMed). This book covers new areas of research such as the use of the analysis of protein content in the CSF to guide the prognosis of patients with severe head injury and/or stroke (currently being tested using technology which can be applied at the bedside to yield results within 15 minutes). With many new or completely revised illustrations, this book serves as not only a reference on the topic, but also a lab manual for bench work with recipes, and a clinical reference on individual diseases. * Introduces the Eastern blotting, the technique considered the "gold standard" by the US Food & Drug Administration (FDA) for the demonstration of IgG by immunofixation following isoelectric focusing * Provides numerous tables for ease-of-use * Extensively cross-referenced with over 1300 references.
Brief Historical Review of CSF Proteins; Functional Glossary; The Roster of CSF Proteins; Differences between Proteins in CSF and Serum; Different Blood-CSF Barriers; Qualitative versus Quantitative Analysis; Methodologies and their Limitations; Fitting the Data to Curves; Normal Blood-CSF Barrier Values.
Originally published as: The CSF proteins. 1988.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cerebrospinal fluid proteins -- Analysis; Nervous system -- Diseases -- Diagnosis; Cerebrospinal fluid proteins -- Diagnostic use; Proteins; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Cerebrospinal Fluid Proteins -- analysis; Nervous System Diseases -- diagnosis; Cerebrospinal fluid proteins -- Analysis; Nervous system -- Diseases -- Diagnosis; Proteins; Electronic books